Importance of multidisciplinary and regional collaboration in integrated West Nile virus surveillance - the "One Health" concept Značaj multidisciplinarne i regionalne suradnje u integriranom nadzoru West Nile virusa - koncept "Jedno zdravlje" - Vilibić Čavlek, Tatjana; Petrović, Tamaš; Savić, Vladimir, veterinar; Šekler, Milanko; Klobučar, Ana, biologinja; Petrić, Dušan; Tabain, Irena; Vidanović, Dejan; Bogdanić, Maja; Lazić, Gospava; Hrnjaković Cvjetković, Ivana; Stevanović, Vladimir, veterinar; et al. (2020)
West Nile virus (WNV) is nowadays one of the most widely distributed arboviruses. In the last two decades, small or large WNV epidemics and epizootics are continuously reported in Europe. In this review, we present the epidemiological characteristics of WNV infections detected in Croatia and Serbia within the “One Health” context. Presented results confirm the importance of multidisciplinary and regional collaboration in the diagnosis and surveillance of this (re-)emerging viral zoonosis.
West Nile virus (WNV) danas je jedan od najrasprostranjenijih arbovirusa. U posljednja se dva desetljeća WNV infekcije kontinuirano pojavljuju na području Europe u obliku manjih ili većih epidemija i epizootija. U ovom preglednom radu prikazujemo epidemiološke značajke WNV infekcija koje su dokazane na području Hrvatske i Srbije u kontekstu “Jednog zdravlja”. Prikazani rezultati potvrđuju značaj multidisciplinarne i regionalne suradnje u dijagnostici i praćenju ove (re-)emergentne virusne zoonoze.
Bibliografija: 52 jed.
Abstract ; Sažetak.
Keywords: Virus zapadnog Nila -- Arbovirusi -- Epidemiološke značajke -- Zoonoze; Hrvatska -- Srbija